Kebijakan Pertahanan Indonesia Terhadap Pulau-Pulau Kecil Terluar Pada Masa Pemerintahan Jokowi - Rambu Asana; Sri Suwartiningsih; Adrianus Bintang Hanto Nugroho (Cakrawala Jurnal Penelitian Sosial, 2017)
From more than 17.506 islands, 92 among them are the outermost small islands which have sea border with ten neighbor states including Malaysia, Singapura, Phillippines, Vietnam, Thailand, Timor-Leste, Papua New Guinea, Republic of Palau, Australia and India. According to The National Agency for Border Management (BNPP), from 92 of the outermost small islands above, 12 are having the vulnerability in security and defense because they were in the outermost coordinate point. Not only because they have sea border with ten neighbor states, but also as regional and global lines. Jokowi with his Global Maritime Axis Doctrine puts the outermost small islands as strategic studies in defense policy. By using constructivism and maritime security concept, the author saw that ideas power transferred by Jokowi through his Global Maritime Axis Doctrine has shaped Indonesian new forms toward how it treat the outermost small islands. Through this research, the author found that Jokowi transfers his idea in Indonesian defense policy successfully, and moreover can make some national constitutions which are based on UNCLOS 1982. The Ministry and/or Institution under Jokowi’s era, such as Ministry of Defense, Ministry of Marine Affairs and Fisheries, and The National Agency for Border Management also played their roles into the outermost small islands. Even though, Indonesian defense policy in Jokowi’s era still far from involvement into the international forum to bring the outermost small islands issues.